A Novel Role of IL13Rα2 in the Pathogenesis of Proliferative Vitreoretinopathy - Qi, Hui; Dong, Lijun; Fang, Dong; Chen, Lu; Wang, Yun; Fan, Ning; Mao, Xingxing; Wu, Wenyi; Yan, Xiaohe; Zhang, Guoming; Zhang, Shaochong; Lei, Hetian (Frontiers in Medicine, 2022)
Proliferative vitreoretinopathy (PVR), an inflammatory and fibrotic blinding disease, is still a therapeutic challenge. Retinal pigment epithelial (RPE) cells dislodged in the vitreous play a central role in the PVR pathogenesis. To identify potential novel contributors to the pathogenesis of PVR, we investigated a profile of vitreous-induced changes in ARPE-19 cells by RNA sequencing. Bioinformatics analysis of the sequencing data showed that there were 258 genes up-regulated and 835 genes down-regulated in the ARPE-19 cells treated with human vitreous. Among these genes, there were three genes related to eye disease with more than threefold changes. In particular, quantitative PCR and western blot results showed that interleukin 13 receptor (IL13R)α2 that is over-expressed in a variety of cancers was up-regulated more than three times in the vitreous-treated ARPE-19 cells. Immunofluorescence analysis indicated that interleukin-13 receptor subunit α2 (IL13Rα2) was highly expressed in ARPE-19 cells within epiretinal membranes from patients with PVR. Importantly, blocking IL13Rα2 with its neutralizing antibody significantly inhibited vitreous-induced contraction of ARPE-19 cells, suggesting a novel role of IL13Rα2 in the PVR pathogenesis. These findings will improve our understanding of the molecular mechanisms by which PVR develops and provides potential targets for PVR therapeutics.